(untitled) (Journal of Medical & Health Sciences Review, 2025)
Dietary practices and nutritional status can affect a person’s health in either a favorable or bad way. The major cause of the bad eating habits of college students is their sensory impressions. In order to evaluate the nutritional status and dietary habits of college students living in Rawalpindi and Islamabad, this research was conducted. The study, which involved 600 students from several institutions in twin cities, was cross-sectional. The technique of purposive sampling was used to gather data. Using a questionnaire that included demographic data, anthropometric measurements, clinical signs and symptoms, and food frequency, the respondents’ nutritional status was evaluated. In order to evaluate the data, SPSS version 23.0 was used. The paired t-test was applied. The confidence interval was chosen at 95% with a significant level at p value <0.05 after frequencies and percentages were computed. Every college student in our study was between the ages of 16 and 18. The nutritional condition of the majority of students (65.3%) was normal. 3.5% were obese, 14.4% were overweight, and 17.8% were underweight. Students’ eating habits showed that those who ate a healthy, balanced diet, were physically active, and slept well had good nutritional status, while those who skipped meals, ate poorly, and were not physically active or slept well were underweight, some were overweight, and a very small percentage were obese. The projected average needs and/or acceptable intakes for all the essential food categories were not met by either gender. It is normal for both male and female students to regularly consume unhealthy foods. It would be advisable that institutions introduce regular programs on nutrition, which are highly emphasized on encouraging proper nutritional habits.